Regional cerebral oxygen saturation variability and brain injury in preterm infants - Ćaleta, Tomislav; Ryll, Martin J.; Bojanić, Katarina; Dessardo, Nada Sindičić; Schroeder, Darrell R.; Sprung, Juraj; Weingarten, Toby N.; Radoš, Milan; Kostović, Ivica; Grizelj, Ruža (Frontiers in Pediatrics, 2024)
Objective: To examine whether variation of regional cerebral oxygen saturation (rScO2) within three days after delivery predicts development of brain injury (intraventricular/cerebellar hemorrhage or white matter injury) in preterm infants. Study design: A prospective study of neonates <32 weeks gestational age with normal cranial ultrasound admitted between 2018 and 2022. All received rScO2 monitoring with nearinfrared spectroscopy at admission up to 72 hours of life. To assess brain injury a magnetic resonance imaging was performed at term-equivalent age. We assessed the association between rScO2 variability (short-term average real variability, rScO2ARV, and standard deviation, rScO2SD), mean rScO2 (rScO2MEAN), and percentage of time rScO2 spent below 60% (rScO2TIME<60%) during the first 72 hours of life and brain injury. Results: The median [IQR] time from birth to brain imaging was 68 [59-79] days. Of 81 neonates, 49 had some form of brain injury. Compared to neonates without injury, in those with injury rScO2ARV was higher during the first 24 hours (P=0.026); rScO2SD was higher at 24 and 72 hours (P= 0.029 and P=0.030, respectively), rScO2MEAN was lower at 48 hours (P=0.042), and rScO2TIME<60% was longer at 24, 48, and 72 hours (P=0.050, P=0.041, and P=0.009, respectively). Similar results were observed in multivariable logistic regression.Although not all results were statistically significant, increased rScO2 variability (rScO2ARV and rScO2SD) and lower mean values of rScO2 were associated with increased likelihood of brain injury. Conclusions: In preterm infants increased aberration of rScO2 in early postdelivery period was associated with an increased likelihood of brain injury diagnosis at term-equivalent age.